Challenges and Opportunities for the Young Generation in Sustainable Agricultural Development - Priani, Gisca Wahyu; Rozaki, Zuhud; Wulandari, Retno; Azzahra, Isni (Universitas Muhammadiyah Yogyakarta, 2024)
Young people around the world face significant challenges and opportunities in taking a key role in sustainable agricultural development. The growth of the agricultural sector is facing serious challenges, especially with a significant decline in the number of young farmers and an increase in old age farmers. The Journal aims to detail the structural changes of the agricultural workforce with a focus on the phenomenon of peasant aging and the decline of young farmers. In addition, the journal will identify the factors causing such changes and detail the policies needed to support the involvement of young farmers in the agricultural sector. The research methods used include descriptive analysis and data tabulation, with the results of the analysis showing that these challenges are getting worse in Indonesia. Several factors caused the decline in the number of farmers in the agricultural sector, including agricultural modernization, social change, lack of profits, the approach of retirement age. One of the Indonesian government's strategies to overcome the challenges of the younger generation industry is through the development of technology-based startups by providing business incubation facilities. The results of this study show that the lack of young workers in the agricultural sector is due to a lack of interest and confidence in the agricultural sector which is considered less promising for the future. However, young workers in the agricultural sector are needed to maintain and advance food in Indonesia. The crisis of young farmers must be addressed so as not to threaten Indonesia. The crisis of young farmers must be addressed so as not to threaten Indonesia's food security, food security is a strategic aspect, and experience in various countries shows that successful development often depends on previous food security achievements.